Canadian Occupational Performance Measure Supported by Talking Mats: An Evaluation of the Clinical Utility - Vita Hagelskjær; Mette Krohn; Pia Susanne Christensen; Jeanette Reffstrup Christensen (Occupational Therapy International)
Background. Some clients with cognitive and communicative impairments after a brain injury are unable to participate in the Canadian Occupational Performance Measure (COPM) without support. The study originates from an assumption that some of these clients are able to participate independently in the COPM interview by using a visual material. Aim. The aim was to investigate the clinical utility of COPM supported by Talking Mats (TM) for community-based clients with cognitive and communicative impairments. Methods. Six clients (51–60 years) were included. After matching the visual material of TM to COPM, the COPM interview was administered twice with an interval of 10 days, once using TM and once without. Interviews were videotaped and studied by six evaluators. Results. The most obvious benefits of using TM as a supportive tool in the COPM interview were related to the first two steps of the COPM interview. Conclusion. Using TM in the COPM interview with clients with cognitive and communicative impairments after a brain injury is recommended as the basis for goal setting. The present study demonstrates a possibility to include a COPM interview to clients who had not been able to complete a COPM interview and thus start a rehabilitation process in a client-centered manner.